2017
DOI: 10.1200/jco.2017.74.1165
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Cardiac Function and Quality of Life for Patients in NSABP Protocol B-31/NRG Oncology: A Randomized Trial Comparing the Safety and Efficacy of Doxorubicin and Cyclophosphamide (AC) Followed by Paclitaxel With AC Followed by Paclitaxel and Trastuzumab in Patients With Node-Positive Breast Cancer With Tumors Overexpressing Human Epidermal Growth Factor Receptor 2

Abstract: Purpose Early cardiac toxicity is a risk associated with adjuvant chemotherapy plus trastuzumab. However, objective measures of cardiac function and health-related quality of life are lacking in long-term follow-up of patients who remain cancer free after completion of adjuvant treatment. Patients and Methods Patients in NSABP Protocol B-31 received anthracycline and taxane chemotherapy with or without trastuzumab for adjuvant treatment of node-positive, human epidermal growth factor receptor 2-positive early-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Most of the pivotal adjuvant trials used anthracycline‐based chemotherapy. In the recently reported update of the National Surgical Adjuvant Breast and Bowel Project B‐31 trial, at a median follow‐up of 8.8 years, the addition of trastuzumab to adjuvant anthracycline‐based and‐taxane‐based chemotherapy did not result in long‐term worsening of cardiac function, cardiac symptoms, or health‐related quality of life in patients without underlying cardiac disease at baseline . However, 5‐10% of patients in the B‐31 trial and the North Central Cancer Treatment Group N9831 trial could not start adjuvant trastuzumab because of a decline in left ventricular ejection fraction that occurred after completion of anthracyclines .…”
Section: Trastuzumab a Landmark In The Treatment Of Her2‐positive DImentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the pivotal adjuvant trials used anthracycline‐based chemotherapy. In the recently reported update of the National Surgical Adjuvant Breast and Bowel Project B‐31 trial, at a median follow‐up of 8.8 years, the addition of trastuzumab to adjuvant anthracycline‐based and‐taxane‐based chemotherapy did not result in long‐term worsening of cardiac function, cardiac symptoms, or health‐related quality of life in patients without underlying cardiac disease at baseline . However, 5‐10% of patients in the B‐31 trial and the North Central Cancer Treatment Group N9831 trial could not start adjuvant trastuzumab because of a decline in left ventricular ejection fraction that occurred after completion of anthracyclines .…”
Section: Trastuzumab a Landmark In The Treatment Of Her2‐positive DImentioning
confidence: 99%
“…Cancer December 1, 2018 B-31 trial, at a median follow-up of 8.8 years, the addition of trastuzumab to adjuvant anthracycline-based andtaxane-based chemotherapy did not result in long-term worsening of cardiac function, cardiac symptoms, or health-related quality of life in patients without underlying cardiac disease at baseline. 12 However, 5-10% of patients in the B-31 trial and the North Central Cancer Treatment Group N9831 trial could not start adjuvant trastuzumab because of a decline in left ventricular ejection fraction that occurred after completion of anthracyclines. 4,7 Breast Cancer International Research Group 006 study 5 is the only adjuvant trial to examine a nonanthracycline-based treatment.…”
Section: Is There An Optimal Way To Combine Trastuzumab With Chemothementioning
confidence: 99%
“…Paclitaxel is a frontline antineoplastic agent widely applied in the treatment of BC, ovarian cancer, gastric cancer, and lung cancer. 20 - 23 In this study, compared with nonpaclitaxel-treated patients with BC, paclitaxel can upregulate the proportion of macrophages in the tumor-infiltrating cells of tumor microenvironment in paclitaxel-treated patients with BC. Similar results have shown that paclitaxel may restore tumor-induced macrophages production of proimmune factors (eg, immunostimulatory cytokine IL-12) in tumor-bearing host.…”
Section: Discussionmentioning
confidence: 80%
“…Paclitaxel is a standard component of therapy in breast, ovarian, lung and cervical and pancreatic cancer. The safety profile of paclitaxel is acceptable even in the treatment of pregnant women during their second and third trimesters of pregnancy, without adverse effects on fetal development, and paclitaxel treatment for breast cancer does not increase cardiovascular mortality [34,35]. Compared to the above, a very low dose of paclitaxel is given in the treatment of PAD, and it is difficult to rationally explain a possible effect with increased mortality.…”
Section: Discussionmentioning
confidence: 99%